Bi-interior, quasi-interior and bi-quasi-interior Γ-hyperideal in Γ-semihyperring - Chaitanya B. Kumbharde; Kishor F. Pawar; Safoora J. Ansari (Journal of Hyperstructures, 2023)
The concept of a Γ-semihyperring is a generalization of a semiring, semihyperring, Γ-semiring. In this Paper we introducethe notion of bi-interior Γ-hyperideals, quasi-interior Γ-hyperideals and bi-quasi-interior Γ-hyperideals in a Γ-semihyperring as a generalization of Γ-hyperideal, left-Γ-hyperideal, right-Γ- hyperideals, bi Γ-hyperideal, quasi Γ-hyperideal, interior Γ-hyperideals of Γ-semihyperring. We studied the properties of these Γ-hyperideals and characterized them in simple Γ-semihyperring and regular Γ-semihyperring